Analysis of Business Success Determinants: The Role of Entrepreneurial Competence, Capital Aspects, and Regional Origin - Mumu, Noldy D. P.; Sayd, Anastasia Imelda; Behi, Hendrik (Public Policy, 2025)
This study investigates the determinants of business success among retail traders in Kupang, focusing on entrepreneurial competence, capital aspects, and regional origin within the framework of social capital theory. Using a quantitative associative approach, data were collected through observation, questionnaires, interviews, and documentation. The findings reveal that entrepreneurial competence has a positive and significant effect on business success, capital aspects have a positive but insignificant effect, and regional origin exerts a negative and significant effect. Contrary to social capital theory, the results suggest that the greater social capital possessed by non-migrant traders does not enhance, but instead hinders, their business success.